5‐T and 6‐T thermometer‐code latches for thermometer‐code shift‐register. Issue 5 (7th July 2021) - Woo, Ki‐Chan; Yang, Byung‐Do
Abstract: This paper proposes thermometer‐code latches having five and six transistors for unidirectional and bidirectional thermometer‐code shift‐registers, respectively. The proposed latches omit the set and reset transistors by changing from two supply voltage nodes to the set and reset signals in the cross‐coupled inverter. They set or reset the data by changing the supply voltage to ground in either of two inverters. They reduce the number of transistors to five and six compared with the conventional thermometer‐code latches having six and eight transistors, respectively. The proposed thermometer‐code latches were simulated using a 65 nm complementary metal‐oxide‐semiconductor (CMOS) process. For comparison, the proposed and conventional latches are adapted to the 64 bit thermometer‐code shift‐registers. The proposed unidirectional and bidirectional shift‐registers occupy 140 μm 2 and 197 μm 2, respectively. Their consumption powers are 4.6 μW and 5.3 μW at a 100 MHz clock frequency with the supply voltage of 1.2 V. They decrease the areas by 16% and 13% compared with the conventional thermometer‐code shift‐register.